2015
DOI: 10.3168/jds.2014-9238
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum quality affects immune system establishment and intestinal development of neonatal calves

Abstract: The first meal of a neonatal calf after birth is crucial for survival and health. The present experiment was performed to assess the effects of colostrum quality on IgG passive transfer, immune and antioxidant status, and intestinal morphology and histology in neonatal calves. Twenty-eight Holstein neonatal male calves were used in the current study, 24 of which were assigned to 1 of 3 treatment groups: those that received colostrum (GrC), transitional milk (GrT, which was obtained after the first milking on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 49 publications
4
72
0
4
Order By: Relevance
“…Thus, the results of the above authors and the result of the present work support the hypothesis that colostrum with high IgG concentration may interfere significantly with intestinal absorptive mucosa, decreasing intestinal absorptive area in the first 72 hr of life. Yang, Zou, Wu, Li, and Cao (), in turn, observed that calves receiving colostrum showed higher villus height, crypt depth and muscle layers thickness compared to calves receiving transition milk at 7 days of life. Steinhoff‐Wagner et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the results of the above authors and the result of the present work support the hypothesis that colostrum with high IgG concentration may interfere significantly with intestinal absorptive mucosa, decreasing intestinal absorptive area in the first 72 hr of life. Yang, Zou, Wu, Li, and Cao (), in turn, observed that calves receiving colostrum showed higher villus height, crypt depth and muscle layers thickness compared to calves receiving transition milk at 7 days of life. Steinhoff‐Wagner et al.…”
Section: Discussionmentioning
confidence: 97%
“…Considering intestinal cell renewal within three to 4 days (Sangild, ), the results of Yang et al. () and Steinhoff‐Wagner et al. () indicate the possibility of a lower rate of cell turnover in an attempt to maintain a first generation of epithelial cells that have the ability to absorb macromolecules, revealing that different mechanisms regulate the development and growth of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…These hormones promote gastrointestinal tract development, production of digestive enzymes, and absorption capacity of nutrients (Bach, 2012). Yang et al (2015) providing for 28 newborn calves first milking colostrum, transitional milk or bulk tank milk (4 L immediately after birth and then 2 L at 8 h after birth) reported that calves fed high quality colostrum presented higher IgG absorption at 24 and 48 h after feeding as compared to transitional milk or bulk tank milk. Additionally, in the first week calves fed first milking colostrum also presented higher antioxidant activities and serum growth factors, villus length and width, crypt depth, and mucosal thickness as compared to transitional milk or bulk tank milk.…”
Section: Colostrum As An Energy Source For Newborn Calves' Thermogenesismentioning
confidence: 99%
“…Colostrum is responsible for the proper functioning of the immune system. It stimulates the digestive system and facilitates the removal of the first fetal stool (meconium) . The effectiveness of colostrum is determined by the time of administration and the level of immune proteins .…”
Section: Introductionmentioning
confidence: 99%
“…It stimulates the digestive system and facilitates the removal of the first fetal stool (meconium). 13,14 The effectiveness of colostrum is determined by the time of administration and the level of immune proteins. 3 A calf up to 6 h after birth should receive the first portion of colostrum, with an average content of 150-200 g of immunoglobulin.…”
Section: Introductionmentioning
confidence: 99%